Performance and modelling of transverse rumble strips on noise and vibration stimuli - Othman, Mohd. Hanifi (2016)
Transverse rumble strips (TRS) are commonly used in reducing vehicle speed and increasing drivers’ alertness on roadway through optical, sound and vibration effects. However, when inappropriately designed, TRS sound and vibration may become too excessive, thus compromise road users’ comfort and annoy local residents who live adjacent to the roadway. This study aims to contribute to the knowledge that will be used to improve the optimisation of TRS cross-section design for road user’s comfort and sustainable living of the neighbourhood. The objectives of this study were to: classify TRS profiles and assess the noise annoyance response towards TRS noise; measure and model TRS roadside noise level and analyse the possible tyre-TRS interaction mechanisms that involved in the TRS roadside noise generation; evaluate and estimate vehicle in-cabin TRS sound and vibration; develop the optimum TRS cross section design for road users’ comfort. Site investigation and social survey study had been carried out to classify the type of TRS profile used on the roadway and to assess the noise annoyance response towards TRS noise experienced by neighbourhood. Traffic noise assessment and controlled pass-by method were carried out to evaluate and estimate roadside noise level due to TRS and to analyse the possible tyre-TRS vibration mechanisms that were involved in the generation of TRS noise. In-cabin sound and vibration measurements were conducted to evaluate incabin vibration and sound due to TRS. Weber’s Law was used to determine appropriate vibration to road user comfort, hence optimum TRS cross section design was proposed. The results indicated that three main types of TRS profile existed on the road namely; raised rumbler, middle overlap and multi-layer overlap. Generally, respondents were annoyed with TRS noise. TRS noise depended on the factor of traffic volume, speed, TRS profile and thickness. TRS vibration depended on the factor of vehicle speed and TRS thickness. Raised rumbler’s profile generated the highest noise as a result from air pumping tyre-pavement mechanism. TRS optimum cross section design was proposed to enhance TRS performance in providing appropriate vibration to road user.